Mepolizumab treatment alters the functional phenotype of eosinophils in severe eosinophilic asthma - Miguéns-Suárez, Pablo; Martelo-Vidal, Laura; Vázquez-Mera, Sara; Blanco-Aparicio, Marina; Calvo-Álvarez, Uxío; González-Fernández, Coral; Mosteiro-Añón, Mar; Corbacho-Abelaira, Dolores; Hermida-Valverde, Tamara; Calvo-Henríquez, Christian; Nieto-Fontarigo, Juan J.; Salgado, Francisco J.; et al. (Frontiers in Immunology, 2025)
BackgroundBlood eosinophil count is usually employed as a predictive and response biomarker for mepolizumab treatment. However, its decrease is not always associated with an improvement in asthma symptoms. The aim of this work is to study the effect of mepolizumab in the activation status and functional phenotype of circulating eosinophils.MethodsSamples from healthy controls (N = 15) and patients with severe eosinophilic asthma (N = 15) before and after 4, 16 and 32 weeks of mepolizumab treatment (anti-IL5 mAb; 100 mg s.c./4 weeks) were screened. Demographic, clinical, hematological and biochemical characteristics were collected. Activation and functional phenotype of peripheral blood eosinophils was analyzed by flow cytometry. sCD62L in serum was measured by ELISA. Target mRNAs were quantified by Nanostring.ResultsEosinophils from severe eosinophilic asthma patients showed a higher activation profile (CD11b, CD44 and IL-5Rα expression) compared to healthy subjects. Mepolizumab treatment reduced the number of basophils and eosinophils in peripheral blood. We also found a clear downmodulation on the surface expression (% and MFI) of CD44 and IL-3Rα on eosinophils at week 4, which was maintained through all treatment period (4–32 weeks). The functional phenotype of the remaining eosinophils was also modified with the treatment, showing a reduction of inflammatory eosinophils (iEOS; CD62Llo) percentage without affecting the balance of regulatory subpopulations (CD16dim/hi eosinophils). This was accompanied by a decrease in serum sCD62L levels. mRNA and protein levels showed similar trends for some targets (e.g., IL-5Rα) but not for others (e.g., CD62L).ConclusionsMepolizumab treatment modifies the functional phenotype of eosinophils resulting in a lower percentage of iEOS and reduced activation status. These changes occur at an early time point (4 weeks) and are maintained throughout all treatment period.